Heavy Metal Resistance of Aeromonas hydrophila Isolated from Raw and Drinking Water in Baghdad City - Oleiwi, Sanaa R. (Iraqi Journal of Science, 2022)
A total of 551 water samples (drinking and raw water) were collected In this study, Aeromonas.hydrophila, were detected by biochemical tests and PCR (16s rRNA gene). The results of identification showed that A.hydrophila had recovery rate 63 isolates (49.21%). The results revealed that all A.hydrophila isolates were PCR positive or the 16S rRNA gene and the results of sequencing showed that two isolates of A.hydrophila(local isolates) had percentage similarities 100% with A. hydrophila ATCC 7966 in GenBank database .All strains had a minimal Inhibitory Concentration(MIC) distribution pattern for lead cetate rranged (900-1200 μg/ml), and mercury chloride ranged (40-80 μg /ml).